1993
DOI: 10.1001/archpsyc.1993.01820150062006
|View full text |Cite
|
Sign up to set email alerts
|

A Linkage Study of Chromosome 11q in Schizophrenia

Abstract: The long arm of chromosome 11 is of interest in schizophrenia research because of three independent reports of balanced 11q translocations cosegregating with schizophrenia and other major psychiatric illness in pedigrees. In addition, a number of candidate genes for psychosis are located in the translocated regions. These include the dopamine D2 receptor, porphobilinogen deaminase, which has shown an allelic association with schizophrenia, and neural cell adhesion molecule, a cell surface glycoprotein involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…[87][88][89][90][91][92][93][94][95] A recent large genome-wide scan emphasized the weakness and fragility of linkage reports in schizophrenia, as no linkage appears to be consistently replicable across large studies. 96 The data suggest some positive findings on chromosome 2, 10, and 22 96 as well as X-chromosome findings 97 and thus require additional investigation.…”
Section: Genetics Of Gaba In Schizophreniamentioning
confidence: 99%
“…[87][88][89][90][91][92][93][94][95] A recent large genome-wide scan emphasized the weakness and fragility of linkage reports in schizophrenia, as no linkage appears to be consistently replicable across large studies. 96 The data suggest some positive findings on chromosome 2, 10, and 22 96 as well as X-chromosome findings 97 and thus require additional investigation.…”
Section: Genetics Of Gaba In Schizophreniamentioning
confidence: 99%
“…Other linkage studies have in contrast yielded negative results. 22,23 The previous failure to find linkage in the region of the GRM5 gene may be related to the small effect size seen in this study and illustrates the power of the association approach for such susceptibility loci. A more extensive survey in different cohorts and populations, to determine whether the 197-bp allele is found exclusively in 'at risk' individuals, is now warranted.…”
mentioning
confidence: 61%
“…Previous studies have found linkage to chromosome 8 for these data [23] . Other studies have previously reported findings suggesting the importance of chromosome 11 [24][25][26][27][28][29] and chromosome 13 [30][31][32][33] , and a recent meta-analysis found evidence for linkage to 1, 2q, 3q, 4q, 5q, 8p and 10q [34] . We therefore believe our analysis of susceptibility has probably increased the power of linkage analysis in these data.…”
Section: Discussionmentioning
confidence: 99%